Perencanaan Ruang Publik Berdasarkan Preferensi Masyarakat di Bantaran Sungai Gajah Wong Segmen Kampung Pedak Karangbendo, Bantul, DIY - Saraswati, Amalia Kintan (Media Komunikasi Dunia Ilmu Sipil (MoDuluS), 2024)
Public spaces are a crucial component of any settlement, serving as facilities for social activities among residents, balancing the ecosystem, and enhancing the environmental aesthetics. However, their presence is often neglected, especially in densely populated areas such as riverbanks. This research focuses on planning public spaces in Kampung Pedak Karangbendo, located along the Gajah Wong River in Yogyakarta, which is known as a slum area. According to Regent’s Decree No. 193 of 2021, Kampung Pedak Karangbendo faces various issues such as irregular and dense buildings, as well as a lack of basic facilities. As part of the Kotaku Program implemented by the Bantul Regency Public Works and Housing Agency, a master plan and detailed engineering design (DED) have been prepared to address these settlement issues. However, the plan has not yet included adequate public space provision. This study aims to plan public spaces based on the preferences of the local community, with the hope of creating comfortable and functional spaces for various age groups. The results of this research are expected to provide guidance for planners and policymakers in developing more inclusive and sustainable public spaces along the Gajah Wong River, thereby improving the quality of life and social interactions of the local community